Synthesis and Photothermal Effects of Intracellular Aggregating Nanodrugs Targeting Nasopharyngeal Carcinoma - Zhong, Ying; Bejjanki, Naveen Kumar; Miao, Xiangwan; Weng, Huanhuan; Li, Quanming; Zhang, Juan; Liu, Tao; Vannam, Raghu; Xie, Minqiang (Frontiers in Bioengineering and Biotechnology, 2021)
Chemotherapy for the treatment of nasopharyngeal carcinoma is usually associated with many side effects; therefore, its treatment options have not yet been completely resolved. Improving distribution to the targeted tumor region and enhancing the cellular uptake of drugs can efficiently alleviate the above adverse medical effects. Near-infrared (NIR) laser light-mediated photothermal therapy (PTT) and photodynamic therapy (PDT) are promising strategies for cancer treatment. In the present study, we developed an efficient multifunctional nanocluster (FA-PEG/CBT@SPION-ICG) with enhanced targeting and aggregation efficiency for PTT and PDT that is composed of a biocompatible folic acid (FA)- and indocyanine green (ICG)-doped Cys(StBu)-Lys-CBT functionalized peptide labeled with an aldehyde sodium alginate-modified iron oxide nanoparticle (ASA-MNP)-based nanocarrier. FA can bind to folate receptors on cancer cell membranes to enhance nanocluster uptake. Cys(StBu)-Lys-CBT can react with glutathione (GSH), which is typically present at higher levels in cancer cells, to form intracellular aggregates and increase the local concentration of the nanodrug. In in vitro studies, FA-PEG/CBT@SPION-ICG displayed the desired uptake capacity by HNE-1 nasopharyngeal carcinoma (NPC) cells and the ability to suppress the growth of cancer cells under laser irradiation. Animal studies validated that FA-PEG/CBT@SPION-ICG is safe and nontoxic, efficiently accumulates in NPC tumor sites following injection via the caudal vein, and shows superior inhibition of tumor growth in an HNE-1 tumor-bearing mouse model upon near-infrared laser irradiation. The results indicate the potential application of FA-PEG/CBT@SPION-ICG, which can be used as a new method for the treatment of folate receptor-positive nasopharyngeal carcinoma.